Design and Development of Credenceledger, A Secure, Efficient and Scalable Blockchainbased System for Educational Records Certification, Authentication and Verification - Arenas, Rodelio (Archīum Ateneo, 2020)
Blockchain, the underlying technology that powers cryptocurrencies such as Bitcoin and Ethereum, is gaining attention from different industry stakeholders, governments and research communities. Its application is extending beyond cryptocurrencies and has been leveraged in different domains such as FinTech, E-commerce, Internet of Things (IoT), healthcare, and governance. Some key essential attributes of the technology are decentralization, immutability, security and transparency. This study involves the design and development of a Blockchain-based architecture, named ’CredenceLedger’, to address the missing and unavailable desired features in current verification systems for educational records. This solution also utilized a better searching algorithm by using HashMap and maintained the hashing of data for security. Simulation results validate the significant improvement in the searching efficiency. The architecture also implemented an off-chain storage of non-transactional data to address scalability and storage issues. Off-chain is verified through Merkle proofs and proof root. Numerical analysis demonstrates the significant advantage of the proposed structure. Overall, the CredenceLedger proposed in this study can be a preferred solution for the educational records certification, authentication and verification.